A Three Decades Urban Growth Monitoring in Hadejia, Nigeria Using Remote Sensing and Geospatial Techniques. Issue 1 (January 2021) - Gambo, Jibrin; Ahmed Yusuf, Yusuf; Zulhaidi bin Mohd Shafri, Helmi; Salihu Lay, Usman; Ahmed, Abubakar
Abstract: Overpopulation growth and urban center crowd became a global phenomenon which mainly cause urban growth in both developed and developing countries cities including Nigeria. Understanding the extent and pattern of such growth required spatial information as well as earth observation data that will be analyse on a temporal dimension. Remote sensing data and geospatial approach together with other auxiliary's data were used to detect and monitor the spatio-temporal growth pattern and extent in the three decades of Hadejia town. The aim of this research is to understand how Hadejia town are spatial expand in terms of size and population between the years 1984-2019. Nevertheless, the spatio-temporal analysis over the three decades of 1984, 1999 and 2019 have been made. The research was carried out via remote sensing and geospatial method, satellite data were acquired across the region; atmospheric corrected using QUAC in Envi software; and also produced landuse landcover map. However, the research utilized object based image analysis (OBIA) for image classification and then built-up area were extracted in order to evaluate the urban expansion. The results indicate that the overall urban expansion occurred in between 1999 – 2019 with expansion of 566 hectares. Most of the changes happens along town major highway especial along interstate routes. The city has experienced an extreme growth geographically at East- Northern part due to plain terrain than Southern part because of present of river Hadejia.